Proteomics Used in Identifying Novel Correlates of Disease in Pediatric Metabolic Dysfunction‐Associated Steatotic Liver Disease - Diego Paine‐Cabrera; Lisa K. Harvey; Michele T. Pritchard; John Thyfault; Antonio Artigues; Udayan Apte; Voytek Slowik (Clinical and Translational Science, 2025)
ABSTRACT Metabolic dysfunction‐associated liver disease (MASLD) is a leading cause of liver disease in children. There is a paucity of data on potential biomarkers and therapeutic targets, especially in pediatric MASLD. We used mass spectrometry (MS)‐mediated proteomics followed by enzyme‐linked immunosorbent assay (ELISA) to identify potential biomarkers and therapeutic targets in pediatric MASLD. Serum samples were collected from pediatric subjects without (n = 56) and with MASLD (n = 72). Initial screen using MS‐based proteomics identified 6 upregulated (adenosine deaminase 2, sex hormone‐binding globulin (SHBG), inter‐alpha‐trypsin inhibitor heavy chain H1 (ITIH1), fructose‐bisphosphate aldolase A, type II cytoskeletal 2 epidermal keratine, N‐acetylmuramoyl‐L‐alanine amidase) and 3 downregulated (alcohol dehydrogenase 4 (ADH4), fructose‐bisphosphate aldolase B (ALDOB), serum albumin) proteins in the MASLD group. Confirmatory studies using ELISA were performed for the 2 strongest upregulated proteins (SHBG and ITIH1) and two top downregulated proteins (ADH4 and ALDOB). Correlation of ELISA results with clinical data revealed that SHBG had strong associations with BMI, ALT, and HgbA1c (p < 0.05). ADH4 had strong associations with BMI and HgbA1c (p < 0.05). ITIH1 and ALDOB had no strong correlations with common clinical parameters of MASLD. Area under ROC Curve revealed statistically significant ability of SHBG (494 nmol/L, sensitivity = 98%, specificity 80%) and ADH4 (2.14 ng/mL, sensitivity = 65%, specificity = 66%) to diagnosis MASLD (p < 0.05). MS with confirmation ELISA identified SHBG and ADH4 as potential biomarkers of pediatric MASLD.